Genotype–Phenotype Correlations for ATX-TBP (SCA17): MDSGene Systematic Review - Rossi, Malco Damian (2023)
Spinocerebellar ataxia type 17 or ATX-TBP is a CAG/CAA repeat expansion disorder characterized by marked clinical heterogeneity. Reports of affected carriers with subthreshold repeat expansions and of patients with Parkinson´s disease (PD) with expanded repeats have cast doubt on the established cutoff values of the expansions and the phenotypic spectrum of this disorder. The objective of this systematic review was to explore the genotype-phenotype relationships for repeat expansions in TBP to delineate the ATX-TBP phenotype and reevaluate the pathological range of repeat expansions. The International Parkinson and Movement Disorder Society Genetic Mutation Database (MDSGene) standardized data extraction protocol was followed. Clinically affected carriers of reported ATX-TBP expansions were included. Publications that contained repeat sizes in screened cohorts of patients with PD and/or healthy individuals were included for a separate evaluation of cutoff values. Phenotypic and genotypic data for 346 ATX-TBP patients were curated. Overall, 97.7% of the patients had ≥41 repeats, while 99.6% of patients with PD and 99.9% of healthy individuals had ≤42 repeats, with a gray zone of reduced penetrance between 41 and 45 repeats. Pure parkinsonism was more common in ATX-TBP patients with 41 to 45 repeats than in the group with ≥46 repeats, which conversely more often presented with a complex phenotype with mixed movement disorders. An updated genotype-phenotype assessment for ATX-TBP is provided, and new repeat expansion cutoff values of reduced penetrance (41-45 expanded repeats) and full penetrance (46-66 expanded repeats) are proposed. These adjusted cutoff values will have diagnostic and counseling implications and may guide future clinical trial protocol.